Effectiveness of nurse-run smoking cessation discussions lasting up to 90 minutes: A systematic review and meta-analysis - Winell, Klas; Ahonen, Juha E. (European Publishing, 2026)
Introduction:
It is important that nurses are active in smoking cessation. We studied if cessation discussions by nurses, lasting up to 90 minutes, lead to cessation of smoking.
Methods:
A literature search was made from The Cochrane Central Register of Controlled Trials and MEDLINE. Randomized controlled trials on smoking cessation of adult daily smokers by nurses published from January 1983 to December 2023 were searched with the following defining of intervention: at least once face-to-face contact, a maximum of five contacts, total counselling time of ≤90 minutes, no concurrent cessation medication or physician input. Controls had no nurse counselling. The restricted maximum-likelihood method was used to calculate the odds ratio (OR) without adjustment for individual trials and to estimate the pooled effect. RoB 2 tool was used to assess the bias.
Results:
Seven studies involving 4443 smokers were included. All studies presented some risk of bias, and three were judged to have high overall risk of bias. The pooled analyses favored the controls but without a statistically significant effect at 12 months, biochemically validated abstinence (4295 smokers, six studies, OR=1.22; 95% CI: 0.83–1.80) and self-reported abstinence (3396 smokers, five studies, OR=1.02; 95% CI: 0.65–1.61). Substantial heterogeneity was observed (I2=57% for biochemically validated outcomes; I2=73% for self-reported outcomes).
Conclusions:
Our results of studies on nurse-run counselling lasting ≤90 minutes did not demonstrate effectiveness in promoting smoking cessation. This should be considered while organizing cessation care. Instead, smokers who are interested in using cessation medication should be given more time and offered the possibility to participate in cessation group counselling. Given that many participants in the included studies had long smoking histories and smoking-related illnesses, future RCTs should examine nurse-run cessation interventions in populations with shorter smoking histories and fewer comorbidities.